STRATEGI PEMASARAN DEPOT AIR MINUM ISI ULANG RAJA WATER DALAM MENINGKATKAN PENJUALAN DIGAMPONG PANTE KOTA LHOKSUKON - Rafy Muksalmina; Sufi Sufi (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
The focus and purpose of this research is to find out how the marketing strategy and public perception are in buying interest in selling Raja Water refill drinking water. This study uses a qualitative method. Sources of data used in this study are primary data and secondary data. Data collection is done by using observation, interview, and documentation techniques. The data analysis technique used is technical analysis which consists of three components, namely data reduction, data presentation, and drawing conclusions. From the results of the study, it can be seen that the marketing strategy is quite good and meets all the criteria consisting of customers of the Raja Water refill drinking water depot which has increased in sales in Pante Village, the determination of a business location that is suitable for marketing, the promotion section is still minimal, and limited customer relationship. Then the public perception carried out by the Raja Water refill drinking water depot is that the refill drinking water depot can provide cheaper prices without using promotional vouchers/coupons and provide clean and hygienic water quality and serve customers very well in order to improve buying interest in a consumer.